Red, White, Rain, and Packaged Water: Adaptive Strategies to Clean Water Scarcity in Kepulauan Meranti’s Outermost Islands, Indonesia - Isnaini, Zuli Laili; Hudayana, Bambang; Setiadi, Setiadi; Afriyanti, Dian (Komunitas: International Journal of Indonesian Society and Culture, 2025)
Peat communities in Kepulauan Meranti face clean water scarcity and the lack of a national clean water supply system. We aim to observe local adaptation strategies in response to locally available water resources. We examined two villages (Lukun and Beting) and a city (Kota Selat Panjang), and ethnicities (indigenous Orang Akit, Malay, and Tionghoa) and problems concerning clean water scarcity. We conducted participatory observations and in-depth interviews for two months. We gathered data on water sources, perceptions regarding causes of water scarcity, and adaptation strategies. There are four local water sources. They are peat water (red water), borewell water (white water), rainwater, and packaged water. The perceived quality of these sources is influenced by environmental, religious, cultural, and economic values, affecting each ethnic group’s adaptation strategies. Rainwater is perceived as a clean source accessible to all, but differs in practices to access depending on economic condition. Peat water or rhedang water is perceived differently among the ethnic groups; Orang Akit relies on peat water and perceives it as freely available clean water. The Orang Akit demonstrated notable adaptability to peat water, but they are the most vulnerable community due to limited livelihood. The other two ethnic groups have more access to rainwater and perceive peat water as clean as rainwater. Adaptation to water scarcity in peatland differs in ethnic groups depending on their values and livelihoods.